Enhanced piezoelectric properties and lowered sintering temperature of Ba(Zr0.07Ti0.93)O3 by B2O3 addition - Jarupoom P. (2014)
The effects of B2O3 doping on densification, ferroelectric, and piezoelectric properties of Ba(Zr0.07Ti0.93)O3(BZT) ceramics were investigated. The addition of B2O3 to the ceramics lowered the sintering temperature by ∼200 °C as well as changed their microstructures. Higher B2O3 concentration caused a decrease in remanent polarization and coercive field, while the piezoelectric coefficient d33 remained at a high value of 291 pC/N for the ceramic sample with 2 wt.% B2O3. The relationship between piezoelectric properties and ferroelectric constant was examined. © 2009 Elsevier B.V. All rights reserved.